0515 Interaction Of Apnea Severity And Comorbidity With CPAP Adherence. (12th April 2019) - Schwartz, Skai W; Ghimire-Aryal, Pragati; Scheer, Darren; Taylor, Kenneth; Anderson, W M; Rosas, Julie; Foulis, P R
Abstract: Introduction: While the effects of both the apnea-hypopnea index (AHI) and adherence to continuous positive airway pressure (PAP) have been studied with respect to the incidence of major adverse cardiovascular events (MACE), few studies have directly reported on the interaction between the two. Further, the interaction between PAP adherence and the Charlson morbidity index (CMI) has also not been adequately studied. Methods: This analysis used a cohort of patients who underwent a sleep study and were prescribed PAP at JAH Veterans Hospital in Tampa Florida between 2004 and 2007 and their follow-up data through the end of 2012. PAP adherence in the initial 3 weeks was defined as use for greater than 4 hours per day for 70% of days. MACE included death, unstable angina, MI, stroke, and surgical procedures including angioplasty, bypass and endarterectomy. AHI was entered into Proportion Hazards regression models as a continuous variable. Models were adjusted for demographics, Charlson morbidity score and prior MACE. Results: 1737 patients with complete data for AHA, PAP adherence and covariates were included. There were 323 MACE events within 5 years. The adjusted Hazard Ratio (HRadj) for MACE for a 1 standard deviation increase in AHI was 1.124; 95% CI=(1.004, 1.257). PAP adherence was significantly protective (HRadj = 0.793; 95% CI=(0.628, 1.000). Based on the model, for a fifty-nine year old male Caucasian patient with an AHI of 60, the probability of surviving MACE for 5 years increased from 82% to 86% if adherent to CPAP. For a similar individual but with AHI =15, the probability of surviving MACE for 5 years still increased from 85.2% to 87.4% if adherent to CPAP. Assuming an AHI of 39, the average for this sample, PAP usage increased 5-year survival from 67% to 77% for an individual with comorbidity (CMI = 4), but did not affect survival for individual with no important comorbidity (CMI=0, survival = 92%). Conclusion: Initial CPAP adherence protects against MACE, especially in patients with significant comorbidity. Support (If Any): Supported with the resources and use of facilities at JAH Veteran's Hospital.